This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: HOMEWORK ASSIGNMENT 1: SOLUTIONS TO THE GRADED EXERCISES MATH 115A, SECTION 3, FALL 2011 Ex. 2 (*) Let S be any nonempty set and F be any field, and let F ( S , F ) denote the set of all functions from S to F . Two functions f and g in F ( S , F ) are called equal if f ( s ) = g ( s ) for each s P S . For f , g P F ( S , F ) and c P F , let f + g , cf P F ( S , F ) be the functions defined by ( f + g )( s ) = f ( s ) + g ( s ) ( s P S ) , ( cf )( s ) = cf ( s ) ( s P S ) . Prove the following statements. (a) The operations + and . defined above give F ( S , F ) the structure of a vector space over F . Solution. (VS1) For f , g P F ( S , F ) , f + g = g + f because for each s P S , ( f + g )( s ) = f ( s ) + g ( s ) by definition, and f ( s ) + g ( s ) = g ( s ) + f ( s ) because F is a field; finally g ( s ) + f ( s ) = ( g + f )( s ) by definition. Since this holds for every s P S , we have f + g = g + f . (VS2) is proved in a similar way. The zero vector of (VS3) is the function 0 P F ( S , F ) defined by 0 ( s ) = 0 for every s P S , and we then have f + = f for every f because f ( s ) + ( s ) = f ( s ) + = f ( s ) for every s P S , since F is a field. For (VS4), given f , we let f be the function given by ( f )( s ) = ( f ( s )) for s P S , and then we will have f + ( f ) = because f ( s ) + ( f ( s )) = 0 for every s P S . For (VS5), ( 1 f )( s ) = 1 f ( s ) = f ( s ) for every s P S , and then 1...
View Full
Document
 Fall '08
 Kong,L
 Math

Click to edit the document details